Contraceptive and reproductive health practices of unmarried women globally, 1999 to 2018: Systematic review and meta-analysis. Issue 49 (4th December 2020) - Wang, Meng-yao; Temmerman, Marleen; Zhang, Wei-hong; Fan, Yu; Mu, Yi; Mo, Si-ping; Zheng, Ai; Li, Jin-ke
Abstract: Background: Premarital sex practices and contraceptive prevalence rate (CPR) among unmarried women worldwide remain unclear, even though unmarried women tend to have multiple sex partners over time, which makes their sexual behaviors particularly important to the sexual and reproductive health of society more broadly. Methods: We searched the MEDLINE, PubMed, and Google Scholar databases for relevant articles published between January 1, 1999 and December 31, 2018. Data on prevalence of premarital sexual intercourse, use of highly prevalent contraceptive methods, as well as CPR overall and at first sexual intercourse were extracted and estimated using a DerSimonian– Laird random effects model. Results: Of the 3918 articles identified, 37 covering 19 countries were included. The estimated overall prevalence of premarital sexual intercourse was 41.9% (95%CI 34.2–49.6%). Pooled CPR was 57.0% (95%CI 44.3–69.8%) overall and 57.6% (95% CI 39.5– 75.6%) at first intercourse. The overall prevalence of condom use was 51.2% (95%CI 42.7–59.7%), followed by oral contraceptives (20.5%, 95%CI 13.7–27.3%), withdrawal (12.7%, 95%CI 9.4–15.9%), and rhythm (12.1%, 95%CI 6.7–17.4%). Conclusion: The findings of this global study indicate worrying trends in unprotected intercourse and contraceptive practices, suggesting the need for greater attention and resources aimed at educating unmarried adolescent women about sexual and reproductive health. Systematic review registration number: CRD42019132736.